Aplikasi Etil Selulosa sebagai Polimer pada Formulasi Mikrokapsul Papain dengan Metode Penguapan Pelarut - Yahdian Rasyadi; Farida Rahim; Nadya Fitri Handayani (Jurnal Akademi Farmasi Prayoga, 2019)
Papain is an enzyme obtained from the sap of papaya which has proteolytic power, easily damaged by air both during manufacture and storage. This study aims to see whether microencapsulation of papain using ethyl cellulose by solvent evaporation method can protect papain from damage. Papain microcapsules are made with papain and ethyl cellulose polymers with their respective ratios F1 (1:1), F2 (1:2), F3 (1:3) using solvent evaporation methods. Evaluation of papain microcapsules with ethyl cellulose as a polymer includes organoleptis, particle size average, % recovery, surface morphology of microcapsules using Scanning Electron Microscope (SEM). From the evaluations of organoleptic F1, F2, and F3, three formulas were formed in the form of crystalline powder, yellowish white, distinctive smell. Particle size average of F1; F2; and F3 each of which is 14.68 µm; 42.84 µm; and 70.98 µm. Recovery from F1, F2, and F3 were 85.50%, 93.24% and 95.50% respectively. The results of SEM showed that ethyl cellulose had covered the surface of papain in F1, F2, and F3. The particle size and % recovery show that F3 is the best formula. Papain microencapsulation using ethyl cellulose by solvent evaporation method can provide protection against papain from damage.